Consumer perception on MPH Bookstores service marketing towards achieving customer satisfaction / Nurul Soleha Hashim - Hashim, Nurul Soleha (Faculty of Business and Management, 2018)
Because of the trouble, most bookstores were facing, the researcher proposed a factor that contributes to the success of customer satisfaction. With this, the study aimed to look into the relationship of that factor that leads to customer satisfaction. After which, it looked into the relationship of this variable towards the service marketing. It found four variable towards particularly ambient condition, staff attitude, service quality and product availability at MPH Bookstores. The researcher was able to gather 230 respondents from the customers who had experience in buying books at MPH Bookstores Publika. Respondents of the study will be selected using convenience sampling. After data collection, Statistical Package for the Social Sciences (SPSS) will be employed for data analysis. The data find shows all the variable are positively correlated with customer satisfaction. Overall, the result of the study is important for marketers to identify the important factors that influence customer satisfaction with service marketing at Bookstores.